Literatura, história e senso comum: Lima Barreto e suas representações do músico popular - Isadora Almeida Rodrigues (2013)
The place that Brazilian popular urban music occupies in the imaginary of this countrys population and its importance for the cultural scenario has not always been similar to the configurations known by our post-bossa nova society. If, nowadays, samba and the acoustic guitar are major symbols of our national cultural identity, one hundred years ago the context was very different. Popular music, in the beginnings of the XXth century, was victim of a great amount of prejudice, as it was not accepted as an art and was relegated to the periphery. With this acknowledgement came the curiosity on a better comprehension of this other Brazilian cultural context and, for such, I have chosen to investigate how this issue is discussed in literary texts of the time. Lima Barreto, who is usually associated to alterity, to deviation of common sense, was one of the few writers who decided to dedicate part of their texts to the theme of popular music. This fact was the main reason why his oeuvre mainly the novels Triste fim de Policarpo Quaresma and Clara dos Anjos has been chosen as the object of this research. If Lima Barretos literature is usually characterized as deviant to common sense and to prejudice in several of its forms, this does not seem to happen in the case of Brazilian popular music. In this particular matter, the author ends up reproducing the prejudices, depicting popular music and the popular musicians as negative elements for society. Thus, the objective of this text was to conduct a better investigation of how Lima Barreto saw Brazilian popular urban music and how his perspective can be related to the common sense on such issue. As a result, It was verified that the authors prejudice when it comes to popular music manifestations was very strong. As the final thought of this research, one important question is asked: Is there still elitism and prejudice in regards to popular urban music?